Conductive waterborne silicone acrylate emulsion/carbon nanotubes composite coatings: preparation and characterization. Issue 7 (3rd July 2021) - Li, Cen; Yan, Zhangyin; Zhang, Yufei; Qi, Lin; Ge, Shengsong; Shao, Qian
Abstract: Common organic coatings are hardly conductive and seldom applied in electromagnetic shielding fields. Thereby, the thermoplastic conductive nanocomposites, waterborne silicon-acrylic emulsion (SAE) merged with multi-walled carbon nanotubes (MWCNTs) and silica sols (Si), were prepared via co-blending method. Compared with neat SAE, the conductivity of composite latex (5 wt.% MWCNT and 1.5 wt.% Si) was raised nearly seven orders of magnitude, and the tensile strength and Young's modulus were enhanced to 366% and 177%, respectively. The contact angle was raised from 59° to 84°. The curing temperature was decreased by 12.8 °C. These enhancements proved that the addition of MWCNTs and silica sol could boost the electrical, mechanical, curing, heatproof and waterproof performances of SAE, which will be employed in high-property conductive paint areas, including the flexible and stretchable devices. Graphical Abstract: UF0001